2014
DOI: 10.1016/j.tcb.2014.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Architectural proteins: regulators of 3D genome organization in cell fate

Abstract: The relationship between alterations in chromatin structure and changes in gene expression during cell differentiation has served as a paradigm to understand the link between genome organization and function. Yet the factors involved and the mechanisms by which the three-dimensional organization of the nucleus is established remain poorly understood. The use of Chromosome Conformation-Capture (3C) based approaches has resulted in a new appreciation of the role of architectural proteins in the establishment of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
68
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(73 citation statements)
references
References 82 publications
4
68
0
1
Order By: Relevance
“…Our observations are also consistent with the possibility of E␤ scanning the chromatin by making several less-frequent/unstable random contacts with other elements within its target domain and restriction of the target domain by the intervening insulator. This is consistent with the emerging views that dynamic interactions of a variable frequency occur within chromatin domains; interactions between enhancers and their cognate promoters are most frequent and/or stable but may be modulated by CTCF-binding sites residing within the same topologically associated domains (TADs) (40).…”
Section: Pdβ1-djcβ1supporting
confidence: 89%
“…Our observations are also consistent with the possibility of E␤ scanning the chromatin by making several less-frequent/unstable random contacts with other elements within its target domain and restriction of the target domain by the intervening insulator. This is consistent with the emerging views that dynamic interactions of a variable frequency occur within chromatin domains; interactions between enhancers and their cognate promoters are most frequent and/or stable but may be modulated by CTCF-binding sites residing within the same topologically associated domains (TADs) (40).…”
Section: Pdβ1-djcβ1supporting
confidence: 89%
“…This particular region of HoxD, located between genes strongly and constitutively interacting with either the centromeric (Hoxd13) or the telomeric (Hoxd1, Hoxd4) TADs, may thus display more flexibility, perhaps reflected by the capacity of Hoxd8 or Hoxd12 to switch their contacts from one TAD to the other in various limb cell-types (16). Interestingly, this region is strongly enriched in binding sites for architectural proteins such as CCCTC-binding factor (CTCF) and cohesin (41,42), which are known for their capacity to organize genomic boundaries and domains, in particular at TAD boundaries (43). Whether the presence of several sites bound by CTCF in the sequence targeted by the Hoxd8 to Hoxd12 fosmid play a role in the elongation observed by STORM remains to be tested, however, as CTCF-driven interactions would be expected to increase compaction, rather than the opposite.…”
Section: Discussionmentioning
confidence: 99%
“…Besides the large blocks of DNA hypomethylation (Hansen et al 2011;Berman et al 2012;Hon et al 2012;Timp et al 2014) and hypermethylation Coolen et al 2010;Forn et al 2013), other alterations as the activation of gene clusters (Bert et al 2013) and the increased somatic mutation rates observed in heterochromatic and late replicating regions (Schuster-Böckler and Lehner 2012;Polak et al 2015) point out that factors regulating high-order chromatin architecture (Dekker et al 2013;Gómez-Díaz and Corces 2014;Feinberg et al 2016) might play a principal role in the remodeling of the cancer genome (Rodriguez et al 2008a;Lizardi et al 2011;Kemp et al 2014;Lay et al 2015;Taberlay et al 2016). The contribution of Alu repeats to the setting and maintenance of chromatin domains and their regulation in normal and cancer cells is still unknown.…”
Section: Alu-related Determinants Of Global Genomic Hypomethylation Amentioning
confidence: 99%